Combinatorial Peptide Library Protocols - Cabilly, Shmuel; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 1998)
Shmuel Cabilly presents in Combinatorial Peptide Library Protocols a collection of new and unique techniques for the construction and use of peptide libraries. These powerful methods-often detailed here by their pioneers-include protocols for the chemical synthesis of peptide libraries, for constructing peptide libraries that are displayed on the surface of filamentous phage or bacteria, and for the rapid screening of these libraries for molecules with biospecific properties. Additional methods permit identifying specific enzyme substrates, investigating the recognition spectra of various binding proteins, epitope mapping, and identifying mimotopes. Combinatorial Peptide Library Protocols offers novice and experienced investigators alike the ability to select molecules from a randomized pool having specific biological activities. Its state-of-the-art techniques, combined with clear step-by-step instructions, make this book an essential tool in the selection of peptides suitable for drug development.
Synthesis of a One-Bead One-Compound Combinatorial Peptide Library -- Enzyme-Linked Calorimetric Screening of a One-Bead One-Compound Combinatorial Library -- Synthesis and Screening of Positional Scanning Combinatorial Libraries -- Synthesis and Screening of Peptide Libraries on Continuous Cellulose Membrane Supports -- Peralkylation -- to Combinatorial Solid-Phase Assays for Enzyme Activity and Inhibition -- Preparation of Biocompatible Resins for Library Syntheses -- Intramolecular Fluorescence-Quenched Substrate Libraries -- The Solid-Phase Enzyme Inhibitor Library Assay -- Determination of Peptide Substrate Motifs for Protein Kinases Using a “One-Bead One-Compound” Combinatorial Library Approach -- The Use of Peptide Library for the Determination of Kinase Peptide Substrates -- Analysis of Protein Kinase Substrate Specificity by the Use of Peptide Libraries on Cellulose Paper (SPOT-Method) -- Generation of Multiuse Peptide Libraries for Functional Screenings -- Functional Screening of Multiuse Peptide Libraries Using Melanophore Bioassay -- The Basic Structure of Filamentous Phage and Its Use in the Display of Combinatorial Peptide Libraries -- Construction and Use of a 20-mer Phage Display Epitope Library -- Construction of Disulfide-Constrained Random Peptide Libraries Displayed on Phage Coat Protein VIII -- Conformational Mimicry Through Random Constraints Plus Affinity Selection -- The Use of Combinatorial Libraries to Identify Ligands That Interact with Surface Receptors in Living Cells -- Screening Phage Display Peptide Libraries on Nitrocellulose Membranes -- Identification of Disease-Specific Epitopes -- Identification of Peptide Ligands for the Antigen Binding Receptor Expressed on Human B-Cell Lymphomas -- Major Histocompatibility Complex Allele-Specific Peptide Libraries and Identification of T-Cell Mimotopes -- Phage Display of Peptide Libraries on Protein Scaffolds -- Displaying Libraries of Conformationally Constrained Peptides on the Surface of Escherichia coli as Flagellin Fusions -- Combinatorial Peptide Library as an Immunogen.
Keywords: Biochemistry; Biochemistry, general